AFROFUTURIST PROJECTIONS: CULTURAL IDENTITY AND SPECULATIVE FICTION IN NNEDI OKORAFOR'S WHO FEARS DEATH - Kaur, Sukhpreet; Rani, Manju (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This research paper explores Nnedi Okorafor's seminal work, Who Fears Death, through the interdisciplinary lenses of Afrofuturism, identity theory, and speculative fiction. Drawing on the theoretical frameworks of Mark Dery's Afrofuturist theory and Stuart Hall's identity theory, the paper aims to comprehensively analyse how Okorafor reimagines African identities within the context of speculative fiction. Through a close reading of Who Fears Death, the paper examines how Okorafor integrates elements of African culture, mythology, and futurism to create a richly imagined world that challenges traditional narratives and stereotypes. Central to this analysis is an exploration of how the novel engages with themes of race, gender, power, and technology, and how it contributes to the broader Afrofuturist conversation about the future of people of African descent. The paper also investigates how characters in Who Fears Death, particularly the protagonist Onyesonwu, navigate questions of identity within the speculative context of the narrative. By applying Stuart Hall's concept of identity as a fluid and processual phenomenon, the paper explores how characters negotiate their racial, cultural, gendered, and supernatural identities about their experiences, relationships, and the broader societal forces in the novel. Overall, this research paper argues that Who Fears Death significantly contributes to Afrofuturist literature and speculative fiction, offering a nuanced exploration of African identities and challenging readers to reimagine the possibilities of the future. Through its interdisciplinary approach, the paper aims to shed light on the complex intersections of culture, identity, and futurism in Okorafor's work, and to stimulate further research and discussion in these areas.